Know your Enemy: Nature and Biochemistry of Obesity - Bjelanović, Jasna; Skrobić, Ognjan (Archives of Pharmacy, 2024)
Obesity represents a serious medical condition and has nowadays reached pandemic proportions. Comorbidities associated with obesity are severe, and affect almost all organ systems. Adipose tissue has several important functions: to provide energy storage, maintain body temperature through the process of thermogenesis, and maintain balance in a variety of metabolic patterns. Adipose tissue is an endocrine organ with numerous biochemical roles, and in obese individuals adipose tissue becomes either hypertrophic or hyperplastic, with impaired function. The immune system activity and metabolic regulation in adipose tissue are extremely related processes. A loss of balance on this axis causes numerous disorders associated with obesity, and the basis of these disorders is insulin resistance, which is a hallmark of obesity. Hormones that are almost exclusively produced in adipocytes and studied in various biochemistry processes are leptin, adiponectin and resistin. Successful treatment of obesity nowadays involves lifestyle and diet modification, pharmacotherapy, mainly with glucagon-like peptide-1 agonists, and bariatric surgery, which remains the most effective treatment method for the selected population of severely obese individuals. Positive effects of bariatric surgery are reflected not only in a restriction of food intake, but in hormonal changes, especially those of gut hormones responsible for hunger regulation and energy metabolism.